Advancing Tissue Decellularized Hydrogels for Engineering Human Organoids. (22nd May 2022) - Moura, Beatriz S.; Monteiro, Maria V.; Ferreira, Luís P.; Lavrador, Pedro; Gaspar, Vítor M.; Mano, João F.
Abstract: The extracellular matrix plays a critical role in bioinstructing cellular self‐assembly and spatial (re)configuration processes that culminate in human organoids in vitro generation and maturation. Considering the importance of the supporting matrix, herein is showcased the most recent advances in the bioengineering of decellularized tissue hydrogels for generating organoids and assembloids. Key design blueprints, characterization methodologies, and extracellular matrix processing toolboxes are comprehensively discussed in light of current advances. Such enabling approaches provide the grounds for engineering next‐generation tissue‐specific hydrogels with close‐to‐native biomolecular signatures and user‐tailored biophysical properties that may potentiate organoids physiomimetic potential. In a forward looking perspective, the combination of tissue‐specific decellularized hydrogels with increasingly complex multicellular assemblies and bottom‐up cell engineering technologies may unravel unprecedented tissue‐like physiological responses and further advance the exploitation of organoids and assembloids as human disease surrogates or as patient‐tailored living therapeutics. Abstract : Bioengineered decellularized tissue hydrogels arise as close‐to‐native supporting matrices for leveraging organoids and assembloids with enhanced and unprecedented physiomimetic and biological potential, further advancing their exploitation as patient‐specific disease models and living therapeutics. This review delineates the most recent advances in the design and bioengineering of such hydrogels, discussing their improvement and upscaling path toward their application in the clinic.